Study on cementitious properties of steel slag - Zhu G.; Hao Y.; Xia C.; Zhang Y.; Hu T.; Sun S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The converter steel slag chemical and mineral components in China’s main steel plants have been analysed in the present paper. The electronic microscope, energy spectrum analysis, X-ray diffraction analysis confirmed the main mineral compositions in the converter slag. Converter slag of different components were grounded to obtain a powder with specific surface area over 400m2/kg, making them to take place some part of the cement in the concrete as the admixture and carry out the standard tests. The results indicate that the converter slag can be used as cementitious materials for construction. Furthermore, physical mechanic and durability tests on the concrete that certain amount of cement be substituted by converter steel slag powder from different steel plants are carried out, the results show that the concrete with partial substitution of steel slag powder has the advantages of higher later period strength, better frost resistance, good wear resistance and lower hydration heat, etc. This study can be used as the technical basis for “Steel Slag Powder Used For Cement And Concrete”, “Steel Slag Portland Cement”, “Low Heat Portland Steel Slag Cement”, “Steel Slag Road Cement” in China, as well as a driving force to the works of steel slag utilization with high-value addition, circular economy, energy conservation and discharge reduction in the iron and steel industry.